Interacting with robots as performers and producers of music - Chamberlain, Alan; Page, Kevin; De Roure, David; Klyne, Graham (2016)
Is it really so strange to think about a robot as something, or perhaps someone that can produce music, as a performer or even as a composer? What happens when robots perform on stage to live audiences, and when they are perceived as intelligent? In this abstract we start to unpack and explicate some of the issues that emerge when the fields of music technology and robotics come together. The aim of this piece of writing is to prompt the Digital Music Research community to engage in debate, in order develop this emerging field of research.